Legal Harmonization of Child Protection in Human Trafficking: A Comparative Study of Indonesian Positive Law and Islamic Law - M. Yusuf; Devrian Ali Putra; Rizka Sari Putri; Muhammad Beni Saputra; Daffa Khari Syafiqi (Islamic Law and Social Issues in Society, 2025)
This study analyzes the legal protection of child victims of human trafficking through a comparative examination of Indonesian positive law and Islamic law, with specific reference to the Jambi District Court Decision Number 566/Pid.Sus/2023/PN.JMB. The judgment in this case prioritized the punishment of the perpetrator while neglecting the crucial aspect of victim recovery. In response, the study proposes a model of legal harmonization, arguing that the integration of Islamic legal values into positive law has the potential to create a more comprehensive child protection system that is better aligned with Indonesia’s socio-cultural realities. The research employs a normative juridical approach, using comparative and case study methods, and draws upon statutory provisions, judicial decisions, Islamic legal literature, and relevant scholarly works. The findings demonstrate that both Indonesian positive law and Islamic law recognize child trafficking as a grave offence; however, positive law tends to emphasize punitive sanctions, while Islamic law highlights spiritual dimensions and community responsibility in addressing exploitation. The key differences lie in philosophical underpinnings, the flexibility of sanctions, and the treatment of victim recovery, with positive law adopting a legal-formal stance and Islamic law stressing holistic, community-based rehabilitation. The study concludes that harmonization between the two systems can strengthen prevention, rehabilitation, and protection mechanisms, producing a more equitable and culturally grounded framework. This study contributes to proposing an integrative model that combines the procedural certainty of positive law with the ethical and spiritual depth of Islamic law, consistent with the spirit of Pancasila and advancing the global discourse on culturally responsive child protection.